Materials and Techniques for Veneering Anterior Teeth Using Composite Restoratives - Samar Sultan; Huda Nasir; Shoaib Razi; Fatima Farhan; Haroon Rashid (ziauddin University, 2020)
Teeth veneering using composite resins are a conservative approach to improve aesthetics of patient. Due to the advancements in material science and improved clinical techniques, it has been made possible to meet the aesthetic needs of the patient. Ceramic-based laminate veneers are very popular to improve the patients smile and newer materials such as zirconia are now being used to fabricate restorations to achieve desirable results. Restoring teeth using conventional techniques i.e. crowns is a very popular method however; may require elective endodontic therapy, which may result in additional loss of tooth structure and could contribute to increased clinical costs. Adhesive dentistry allows us to replicate of the originality of the teeth and preservation of almost all dental tissues. Adhesive dentistry has seen many progresses during the last decade. In the light of least-invasive dentistry, this approach for restorting teeth has allowed the clinicians to perform much more conservative cavity design preparations. The technique relies upon the effectiveness of current enamel-dentine adhesives that have undergone many advances themselves. Indirect techniques as compared to direct techniques offer several advantages and when used effectively, results in better patient satisfaction. The short descriptive review focuses on composite veneering materials, which may be used directly or indirectly, to achieve better aesthetic outcomes. The data was collected through a comprehensive search using the keywords, "Aesthetic Dentistry; Adhesive Dentistry; Composites; Veneering" from PubMed, Medline and Google Scholar, from 2000 to 2019.